Plant diversity in natural forest of Guilan Rural Heritage Museum in Iran - ROYA ABEDI; HASSAN POURBABAEI (Society for Indonesian Biodiversity, 2010)
Abedi R, Pourbabaei H (2010) Plant diversity in natural forest of Guilan Rural Heritage Museum in Iran. Biodiversitas 11: 182-186. The aim of this study was to determine plant species diversity in Guilan Rural Heritage Museum in Iran. Eighty nine sampling plots were sampled based on systematic random method. Data analysis was carried out using diversity indices of richness, diversity (Shannon-Wiener, Simpson, Mc Arthur’s (N1) and Hill’s (N2) and Smith and Wilson’s evenness index (Evar). Results indicated that Rosaceae and Labiatae families have the highest number of species. Quercus castaneifolia and Ruscus hyrcanus were the most dominant woody plants for class of tree and shrub, respectively. Carex divolsa and Viola odorata were dominant herbaceous species. Herbaceous layer had the highest richness, evenness and diversity. Mc Arthur’s N1 index had the highest value among diversity indices.Key words: diversity, richness, evenness, Rural Heritage Museum, Guilan.